2004
DOI: 10.4049/jimmunol.172.2.1256
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine Secretion of Rheumatoid Arthritis Synovial Fibroblasts Stimulated by Toll-Like Receptor 2 Ligands

Abstract: To analyze the role of Toll-like receptors (TLR) in the pathogenesis of rheumatoid arthritis, we have assessed the effects of stimulation of cultured synovial fibroblasts by the TLR-2 ligand bacterial peptidoglycan. By using high density oligonucleotide microarray analysis we identified 74 genes that were up-regulated >2.5-fold. Fourteen CC and CXC chemokine genes were among the genes with the highest up-regulation. Quantitative real-time PCR analysis confirmed up-regulation of granulocyte chemotactic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
142
0
8

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 235 publications
(159 citation statements)
references
References 58 publications
9
142
0
8
Order By: Relevance
“…It suggests that large amounts of CXCL16 may be produced in RA independently of established proinflammatory cytokines. This finding is consistent with results of a recent study showing that RA fibroblasts express CXCL16 directly when stimulated by way of the Toll-like receptor 2 ligand peptidoglycan (65).…”
Section: Discussionsupporting
confidence: 93%
“…It suggests that large amounts of CXCL16 may be produced in RA independently of established proinflammatory cytokines. This finding is consistent with results of a recent study showing that RA fibroblasts express CXCL16 directly when stimulated by way of the Toll-like receptor 2 ligand peptidoglycan (65).…”
Section: Discussionsupporting
confidence: 93%
“…Recently, the adaptor protein MyD88 and its downstream pathway were shown to play a critical role in both spontaneous and carcinogeninduced tumor development [42,43]. Also, in rheumatoid arthritis and psoriasis, several works support evidence of an important role of endogenous TLR ligands that are involved in the induction of inflammation and initiation of diseases [44][45][46]. cPKC inhibitors that inhibit MyD88-dependent inflammatory signals downstream of TLR and IL-1R can be very promising molecules in the treatment of autoimmune inflammatory diseases, as it has been demonstrated with the AEB071 PKC inhibitor on psoriasis [47].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in our experiments, down-regulation of PBEF in RASFs by siRNA not only decreased basal IL-6, MMP-1, and MMP-3 levels but also significantly inhibited TLR ligand-induced production of cytokines and destructive enzymes. TLRs were shown to be key players in inflammatory and destructive processes in RA (3,4,20,25). TLR ligands of microbial origin as well as endogenous TLR ligands were demonstrated to be present in RA synovial fluid as possible drivers of inflammatory processes (1,26).…”
Section: Discussionmentioning
confidence: 99%
“…Activation of cells by microbial components and also by endogenous molecules via pattern recognition receptors, such as Toll-like receptors (TLRs), results in the production of a variety of cytokines, chemokines, and matrix metalloproteinases (MMPs), some of which are characteristically observed in patients with RA (2). We previously reported induction in SFs of the proinflammatory cytokine interleukin-6 (IL-6) and the chemokines IL-8, granulocyte chemotactic protein 2, macrophage chemotactic protein 2, and RANTES by the TLR-2 ligand bacterial peptidoglycan (3,4). In a subsequent study, we demonstrated overexpression of TLR-3 in RA synovial tissue and established that RNA released by necrotic synovial fluid cells can act as endogenous ligand for TLR-3 on cultured RASFs (5).…”
mentioning
confidence: 99%